An analysis of interest in students learning of physical chemistry experiment using Scientific approach - Widinda Normalia Arlianty (International Journal of Science and Applied Science: Conference Series, 2017)
This study was aimed to analyze interest in student learning of physical chemistry experiment on Chemistry Education students, Islamic University of Indonesia. The research was quantitative. The samples of this research were 2nd-semester student academic year 2015. The data learning interest of students were collected by questionnaire and documentation of seven title experimental. Learning interest consisted of three indicators, concluded feeling good, attention and activity in the learning process. The results of this research showed that score mean of feeling good  indicator was  25,9;  score  mean  of attention indicator 17,8, and score mean of  activity indicator 8,41.  Score Mean  students for the questionnaire interest in student learning  was 51,83 and this data was categorized as “good”.